The ISABEL user survey. - Briggs, J.S (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
ISABEL is a web-based clinical decision-support system for use by healthcare professionals. The Web site has been developed by the ISABEL Medical Charity. The system has come to the attention of the Department of Health, which is examining its potential effectiveness in the wider clinical context and exploring options for promoting its wider use in the NHS. The objectives of the work reported here were to review the existing use of ISABEL and to identify impediments to its development. A questionnaire was sent by e-mail to selected users of the system. Based on an analysis of the results (n=519), we found ISABEL to be a useful tool with many users. We believe that there is evidence of its success sufficient to support its continued availability and development. However, the largest hurdles to its increased use are systemic ones witin the NHS and the way services are delivered.